Reformas al Código Tributario respecto a las reclamaciones y recursos administrativos tributarios, por que violan los principios de simplificación, celeridad y eficacia previstos en la constitución - Saavedra Granda, Guilbert Ismael (2016)
Tax administrative procedures in Ecuador, do not provide the necessary guarantees as their processed are very long and not the principles established in the Constitution of the Republic of Ecuador are met, such as administrative simplicity, efficiency, retroactivity, equity, transparency, the taxpayer has the opportunity to claim against the administration itself or exercise their right to effective judicial protection, so that they are recognized their rights, tax justice could fulfill these purposes, as far as the procedural aspects to achieve an equilibrium in the relationship between the taxpayer and the state, but now we have laws that are obsolete and inefficient procedures in outdated laws that favor the Treasury, poor taxpayer service is used, in addition to our tax laws give excessively broad powers to tax authorities creditors who for the fulfillment of its purposes, have exceeded their capacities putting taxpayers at a disadvantage that seriously injured one of the essential pillars of due process as the right to defense. Moreover, when taxpayers are in the need to address a problem with the tax administration must confront Tax Litigation Process, slow or overly formal, hampered by resources that make them even longer governed by provisions which are not always consider their economic capacity or having few times with judges who are specialized in this area of law. As a result of the above, this lack of jurisdictional response timely results in situations of denial of justice, social unrest and distrust of institutions of tax administration and the judiciary. So the processing of administrative procedures and tax litigation processes is necessary to regulate better since the current violate due process rights. In this research work the problems detailed above, where a study of conceptual, doctrinal character is performed and critical legal around time to resolve claims and administrative tax consultations addressed An approach to reality through surveys and interviews with prominent lawyers in professional judicial district of the province of El Oro free exercise is also performed. Finally, conclusions and recommendations and proposed reform are noted, where they pose solutions aimed at correcting the lack of efficiency and speed in resolving claims and tax management consultation, this in order to safeguarding the interests of taxpayers or taxpayers of tax liability, constituting a substantial contribution to this research